A VIEWS OF STUDENTS REGARDING THE USE OF THE E-PORTFOLIO IN THE CREATION OF DESCRIPTIVE TEXT - Ananda Putri Rizkila Janwarini; Zubaedah Wiji Lestari; Paulina Novarita (Universitas Wiralodra, 2023)
This study aimed to describe students' perceptions of using e-portfolio in writing descriptive text and to find out the impact of the use of e-portfolio in writing descriptive text. This research was conducted with a qualitative approach with a case study. The questionnaire, interview, and students’ artifacts were used in collecting the data. The participants in this research were 32 students from first grade (X MIPA) in Mekar Arum senior high school in Bandung, West Java. There were 32 students, consisting of 28 female and four male students, who were involved in this research. The result showed that E-portfolio is easy, efficient, and useful. E-portfolio help students improve their descriptive text writing cognitively. It also had a positive impact on students' writing. It was indicated by their artifacts, in relation to the use of e-portfolios in producing descriptive texts. The students perceived the use of e-portfolio in writing descriptive text as effective in writing descriptive text. It helped them develop in many ways, especially their cognitive writing in descriptive text. This study is limited to the effectiveness of the E-portfolio. It needs further investigation in terms of examining the effectiveness of E-portfolio in teaching descriptive text to more complex variables such as the genre and level of education.